Medical and Social Aspects of Palliative Care for Dementia - Hamidullayevna, Xushvaktova Dilnoza; qizi, Ochilova Nigina Ulug’bek (American Journal of Bioscience and Clinical Integrity, 2024)
In the context of aging of the population, the volume and complexity of problems that need to be solved in order to meet the need for help and support of the elderly increases. The number of elderly people with dementia is increasing. Dementia is one of the main causes of disability and inability to live on their own in older people around the world. This seriously affects not only the patients themselves, but also their families and caregivers. Dementia is a syndrome characterized by impaired memory, impaired thinking and behavior, and decreased ability to perform daily activities. Although dementia mainly affects older people, it is not part of the normal aging process.